Effect of Dexamethasone Versus Diclofenac Sodium after Phacoemulsification with Intraocular Lens Implantation - Tehmina Imdad, Fatima Sidra Tanweer, Ali RazaShamsa Tariq , Bushra Sultana , Noreen Majeed , Faraz Munir Butt (Journal of Rawalpindi Medical College, 2013)
Background: To study anti inflammatory effect of Dexamethasone versus Diclofenac Sodium after phacoemulsification with posterior chamber intraocular lens implantation Method: The study included 232 cases selected at random from the in patient department. They were divided into two groups, 116 in each group. Patients ranged in age from 4th to 7th decade.Group A received non steroidal anti inflammatory drug, diclofenac sodium and group B received steroid, dexamethasone as postoperative anti inflammatory drug. Data related to cells and flare was collected using Haag-Streit slit lamp biomicroscope with 3mm x 1mm oblique slit at high intensity of light and magnification x16 in a dark room. Patients were then asked to follow the specified regimen of 1 drop of drug every 6 hours in operated eye. Patients were followed on day 3, 7 and then after 2 weeks and 4 weeks. Results: The cells on first post operative day ranged mainly from +1 to +4 grades of cells.On subsequent follow up visits the anterior chamber activity recorded separately for each group decreased to zero till the fourth week.The flare on first post operative day ranged mainly from +1 to +3 in severity. On subsequent follow up visits the flare decreased to zero till the fourth week in both groups. Conclusion:Anti inflammatory effect of diclofenac sodium is comparable to a potent steroid dexamethasone.